Do minimum wage hikes lead to employment destruction?: evidence from a regression discontinuity design in Argentina - Abbate, Nicolás Francisco (2023)
In this study, we examine the impact of eight minimum wage increases in Argentina during the early 21st century by analyzing administrative records of registered employment. Utilizing a regression discontinuity design, we compare job separation rates between a group affected by the minimum wage hikes and a control group slightly out of their legal scope. We show that this method improves upon previous methods by reducing the likelihood of Type-I error. Overall, we find that the minimum wage hikes had no significant effect on job separation rates. However, the increases implemented in 2008 resulted in a decrease of 4.8 percentage points (19%) in separations, indicating that the employment effects of minimum wages may not necessarily lead to job loss.